2016
DOI: 10.1021/acs.joc.6b01227
|View full text |Cite
|
Sign up to set email alerts
|

Access to C4-Functionalized Quinolines via Copper-Catalyzed Tandem Annulation of Alkynyl Imines with Diazo Compounds

Abstract: An efficient synthesis of C4-functionalized quinolines through copper-catalyzed tandem annulation of alkynyl imines with diazo compounds is described. This transformation involves an in situ formation of allene and intramolecular electrocyclization, which features high efficiency, mild reaction conditions, easy operation, and broad functional-group tolerance. A wide variety of C4-functionalized quinolines were provided in up to 92% yield for 33 examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In an intriguing application of copper(I)-catalyzed carbenoids derived from diazoesters 85, Cui and co-workers demonstrated that those can be efficiently trapped by alkynylimines 84 to give rise to allene intermediate 87, which undergoes facile 6π-electrocyclization to form quinolines 86. 36 Wu, Jiang, and co-workers reported and unusual, but nevertheless broadly applicable palladium catalyzed oxidative cyclization of ortho-vinylanilines 88 and alkynes 89 with molecular oxygen, in which ultimately a carbon−carbon bond fission of the stilbene unit occurs. 37 A plausible intermediate in this sequence is 91, which subsequently undergoes carbopalladation to complete the quinoline ring structure.…”
Section: ■ Quinolinesmentioning
confidence: 99%
“…In an intriguing application of copper(I)-catalyzed carbenoids derived from diazoesters 85, Cui and co-workers demonstrated that those can be efficiently trapped by alkynylimines 84 to give rise to allene intermediate 87, which undergoes facile 6π-electrocyclization to form quinolines 86. 36 Wu, Jiang, and co-workers reported and unusual, but nevertheless broadly applicable palladium catalyzed oxidative cyclization of ortho-vinylanilines 88 and alkynes 89 with molecular oxygen, in which ultimately a carbon−carbon bond fission of the stilbene unit occurs. 37 A plausible intermediate in this sequence is 91, which subsequently undergoes carbopalladation to complete the quinoline ring structure.…”
Section: ■ Quinolinesmentioning
confidence: 99%
“…In 2006, Cui and co-workers described a copper-catalyzed tandem reaction of alkynyl imines 68 with -diazo esters 20 to provide an efficient method for the synthesis of C4functionalized quinolines 70 (Scheme 21). 27 This reaction involves the in situ formation of allene intermediate 69 followed by 6-electrocyclization and further aromatization to access the target product.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…[9] We questioned whether this open shell reaction mechanism might be translated to other cascade reaction, thereby delivering a general and efficient route to multisubstituted 4quinolones. As part of our ongoing interest in ynone chemistry, [10] we report herein a base-mediated sequential Michael addition/Smiles rearrangement [11] /N-arylation to generate 1,2,3-trisubstituted 4-quinolones in one step.…”
Section: Introductionmentioning
confidence: 99%